Multi-scale dynamics influence the division potential of stomatal lineage ground cells in Arabidopsis - Hannah F. Fung; Gabriel O. Amador; Renee Dale; Yan Gong; Macy Vollbrecht; Joel M. Erberich; Andrea Mair; Dominique C. Bergmann (Nature Communications)
Abstract During development, many precursor lineages are flexible, producing variable numbers and types of progeny cells. What determines whether precursors differentiate or continue dividing? Here we take a quantitative approach that combines long-term live imaging, statistical modeling and computational simulations to probe the developmental flexibility of stomatal lineage ground cells (SLGC) in Arabidopsis leaves. We discover that cell size is a strong predictor of SLGC behaviour and that cell size is linked to division behaviour at multiple spatial scales. At the neighbourhood scale, cell size correlates with the strength of cell-cell signaling, which affects the rate at which SPEECHLESS (SPCH), a division-promoting transcription factor, is degraded. At the subcellular scale, cell size correlates with nuclear size, which modulates the concentration of SPCH in the nucleus. Our work shows how initial differences in SPCH levels are canalized by nuclear size and cell-cell signaling to inform the behaviour of a flexible cell type.